2012
DOI: 10.1177/0261018312439365
|View full text |Cite
|
Sign up to set email alerts
|

Bouncing back? Recession, resilience and everyday lives

Abstract: This paper critically engages with a recent shift towards an emphasis on ‘resilience’ in policy and academic fields. The paper suggests that this shift is problematic for several reasons: that it supports normative value judgements; that it may overemphasize the ability of people to ‘bounce back’ and undervalue the hidden costs of resilience, especially those with gendered dimensions; and that it may be associated with policy prescriptions that shift responsibility for dealing with crisis away from the public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
122
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(124 citation statements)
references
References 29 publications
0
122
0
2
Order By: Relevance
“…Previous research has shown that emergencies tend to catalyse or intensify downward social and economic trajectories (Cutter et al 2008;Cutter et al 2014) and that the poorest groups tend to recover more slowly from disasters (Béné 2013;Deen 2015), whilst a lack of resilience has been identified as a key dimension of the longitudinal experience of vulnerability (Emmel & Hughes 2010). These ideas challenge the notion that resilience "like a muscle which, when exercised, builds both strength and flexibility" (Wilding, 2011: 27), and supports the idea that coping strategies can undermine resilience in the long term (Harrison 2013;Sen 1983). They also emphasise that vulnerability, rather than being simply a 'technical category', is a dynamic characteristic shaped by structural forces (Brown 2015), which can be exacerbated by or addressed through policy measures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has shown that emergencies tend to catalyse or intensify downward social and economic trajectories (Cutter et al 2008;Cutter et al 2014) and that the poorest groups tend to recover more slowly from disasters (Béné 2013;Deen 2015), whilst a lack of resilience has been identified as a key dimension of the longitudinal experience of vulnerability (Emmel & Hughes 2010). These ideas challenge the notion that resilience "like a muscle which, when exercised, builds both strength and flexibility" (Wilding, 2011: 27), and supports the idea that coping strategies can undermine resilience in the long term (Harrison 2013;Sen 1983). They also emphasise that vulnerability, rather than being simply a 'technical category', is a dynamic characteristic shaped by structural forces (Brown 2015), which can be exacerbated by or addressed through policy measures.…”
Section: Discussionmentioning
confidence: 99%
“…The suggested solution is to target particular kinds of support at vulnerable groups, and to gather information from relevant organisations about who is vulnerable and where they are located. This kind of 'special treatment' of vulnerable groups can be seen to "detract attention from the structural forces that disadvantage people" as well as to illustrate that those not classed as vulnerable are seen as autonomous, 'capable' individuals, able to take on the responsibility of increasing their self-sufficiency (Brown, 2015: 64;Harrison 2013).…”
Section: Policy Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea of focusing on how some people stay well is controversial (Harrison 2013;MacKinnon and Derickson 2013). A key criticism is that focusing on how to mitigate the conversion of economic adversity to poor health, rather than on eliminating economic adversity itself, might implicitly condone economic inequality (for an overview of this perspective, see Chapter 15).…”
Section: Resilience and Equigenic Environmentsmentioning
confidence: 99%
“…As Friend and Moench (2013: 102) note, there is a tendency for resilience to be seen as desirable but nonetheless a rather individualised (or household level) quality: '... where resilience is applied in the context of social policy, it can be done so with connotations of enduring adversity, of standing on one's own as the priority, rather than advancing social improvements or addressing structural factors'. Indeed, the 'resilience agenda' may be attractive to, or be co-opted by, interest groups and political perspectives that use it as justification for a focus on the individual at the expense of reduced responsibility the state or the public sphere more broadly (Harrison 2012, Mohaupt 2008). The project of poverty reduction, for example, becomes depoliticised: 'adopting a default position which individualises that which should, in fact involve structural or collective effort for change ' (Boyden and Cooper 2007: 5).…”
mentioning
confidence: 99%